Realisation of a widely tuneable sampled grating DBR laser emitting around 970 nm. Issue 11 (11th May 2017) - Brox, O.; Tawfieq, M.; Della Casa, P.; Ressel, P.; Sumpf, B.; Erbert, G.; Knigge, A.; Weyers, M.; Wenzel, H.
Abstract : Design and fabrication of a monolithic, single aperture widely tuneable diode laser emitting around 970 nm is presented. Overgrown sampled grating Bragg reflectors are applied to setup wavelength selective mirrors. Wavelength tuning is achieved via the Vernier effect with thermal heaters placed on top of the sampled gratings. The 20 nm quasi‐continuous tuning around 970 nm with an optical side mode suppression ratio in excess of 40 dB is demonstrated and an optical output power of more than 30 mW at a pump current of 180 mA is presented.